Synthetic neurosteroids on brain protection - Rey, Mariana (2015)
Neurosteroids, like allopregnanolone and pregnanolone, are endogenous regulators of neuronal excitability. Inside the brain, they are highly selective and potent modulators of GABAA receptor activity. Their anticonvulsant, anesthetics and anxiolytic properties are useful for the treatments of several neurological and psychiatric disorders via reducing the risks of side effects obtained with the commercial drugs. The principal disadvantages of endogenous neurosteroids administration are their rapid metabolism and their low oral bioavailability. Synthetic steroids analogues with major stability or endogenous neurosteroids stimulation synthesis might constitute promising novel strategies for the treatment of several disorders. Numerous studies indicate that the 3α-hydroxyl configuration is the key for binding and activity, but modifications in the steroid nucleus may emphasize different pharmacophores. So far, several synthetic steroids have been developed with successful neurosteroid-like effects. In this work, we summarize the properties of various synthetic steroids probed in trials throughout the analysis of several neurosteroids-like actions.